Isolamento, caracterização da lectina das sementes de Eugenia pyriformis e potencial antimicrobiano - Favero, Adriano (2019)
Lectins are proteins of non-immune origin, which arouse biotechnological interest in the health area, due to their selective and reversible carbohydrate binding capacity, mediating cellular recognition processes. The objective of this work was to extract lectins, determine their specificity to carbohydrates and evaluate the antibacterial potential in the extract and precipitated and dialysated fractions of the seeds of Eugenia pyriformis. The aqueous extraction was performed in phosphate Buffer pH 7.0, 50 mM with NaCl 0.15 M, followed by fractionation with ammonium sulfate in the saturations of 0-40 (FPD 0-40) and 40-80% (FPD 40-80). The phenolic and proteic dosages were performed by the FolinCicalteau and Bradford methods, respectively. For the detection of lectins, the native and thermally denatured samples were subjected to hemagglutinating activity (HA) tests in Human erythrocytes (ABO), by the serial dilution method. The inhibition of the HA of the lectins was rehearsed with the pre-incubation of the native samples with the carbohydrates D (+)-glucose, D(+)galactose, D(+)glucose, D(+)maltose, D(+)mannose, D(+) sucrose, D(+) ribose, D(+) fucose, D(+) arabinose, D(+) glucosamina, D(+) lactose monohydrate , D(+) galactosamine, N-Acetyl-D-glucosamine, D(+) Trehalose dihydrate, D(+) rhamnose e D-(+)-raffinose pentahydrate. The antibacterial assays were performed by means of disc diffusion for the strains: Staphylococcus aureus, Geobacillus stearothermophilus, Pseudomonas aeruginosa, Shigella flexneri, Escherichia coli, Klebsiella sp., Morganella Sp., Serratia sp., Proteus Mirabilis, Enterococcus faecalis, Bacillus cereus, Streptococcus uberis, Streptococcus pyogenes and Streptococcus agalactiae. The dosages revealed that the seeds contain low protein content (1%) and phenols (0.1%). The HA assays of the native samples resulted positive for ABO erythrocytes, with preference for type A and higher HA (1024) for FPD 40-80. After the thermal denaturation of the samples, the activities suffered a considerable decrease, showing that most of the HA is due to the presence of lectins, which presented affinity mainly for D (+)-galactose, D (+)-arabinose, D (+)- lactose monohydrate and D (+)- galactosamine. The antibacterial tests of the native samples obtained formation of inhibition halos for the strains Staphylococcus aureus, Streptococcus uberis, Enterococcus faecalis, Shigella flexneri, Escherichia coli, Klebsiella sp. and Serratia sp., for all tested fractions. The loss of antibacterial activity in denatures samples shows the proteic nature of the compounds responsible for the effect. The diversity of the specificity of carbohydrates in each sample suggests the presence of at least two lectins in the seeds.